2014
DOI: 10.1021/la500389p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metalloporphyrins with High Sensitivity Using Graphene-Enhanced Resonance Raman Scattering

Abstract: Graphene-enhanced resonance Raman scattering (GERRS) was performed for the detection of three different metallo-octaethylporphyrins (M-OEPs; M = 2H, FeCl, and Pt) homogeneously thermal vapor deposited on a graphene surface. GERRS of M-OEPs were measured using three different excitation wavelengths, λ(ex) = 405, 532, and 633 nm, and characterized detail vibrational bands for the identification of M-OEPs. The GERRS spectra of Pt-OEP at λ(ex) = 532 nm showed ~29 and ~162 times signal enhancement ratio on graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…54 Lu et al reported the sensitive and selective detection of DNA and proteins. 55 Some important biomolecules, such as metalloprophyrins, 53 and more complex systems, such as bacteria 52 and stem cells, 56 are successfully lit up under the GERS effect due to their strong interaction with graphene. Xu et al 57 designed a G-SERS tape constructed with a PMMA/ metal/graphene structure, which was used to analyze trace amounts of molecules in an aqueous solution, on a flat surface, and on a cauliflower vegetable surface.…”
Section: Applications Of Gers In Chemical and Bioanalysismentioning
confidence: 99%
“…54 Lu et al reported the sensitive and selective detection of DNA and proteins. 55 Some important biomolecules, such as metalloprophyrins, 53 and more complex systems, such as bacteria 52 and stem cells, 56 are successfully lit up under the GERS effect due to their strong interaction with graphene. Xu et al 57 designed a G-SERS tape constructed with a PMMA/ metal/graphene structure, which was used to analyze trace amounts of molecules in an aqueous solution, on a flat surface, and on a cauliflower vegetable surface.…”
Section: Applications Of Gers In Chemical and Bioanalysismentioning
confidence: 99%
“…A theoretical framework that covers all the experimentally observed phenomena was proposed in 2014 . Due to its molecular sensitivity and selectivity, GERS was also suggested for applications in chemical and biological sensing devices …”
Section: Introductionmentioning
confidence: 99%
“…Kim et al. reported the highly sensitive detection of metalloprophyrins by a homogeneously thermal vapor deposition method on a graphene surface . The combination of graphene and metals also affords more scope for 2D materials.…”
Section: Applications Of Sers To Noble‐metal‐free Materialsmentioning
confidence: 99%